Exploration of xenobiotic metabolism within cell lines used for Tox21 chemical screening. (June 2021) - Qu, Wei; Crizer, David M.; DeVito, Michael J.; Waidyanatha, Suramya; Xia, Menghang; Houck, Keith; Ferguson, Stephen S.
Abstract: The Tox21 Program has investigated thousands of chemicals with high-throughput screening assays using cell-based assays to link thousands of chemicals to individual molecular targets/pathways. However, these systems have been widely criticized for their suspected lack of 'metabolic competence' to bioactivate or detoxify chemical exposures. In this study, 9 cell line backgrounds used in Tox21 assays (i.e., HepG2, HEK293, Hela, HCT116, ME180, CHO-K1, GH3.TRE-Luc, C3H10T1/2 and MCF7) were evaluated via metabolite formation rates, along with metabolic clearance and metabolite profiling for HepG2, HEK293, and MCF-7aroERE, in comparison to pooled donor (50) suspensions of primary human hepatocytes (PHHs). Using prototype clinical drug substrates for CYP1A2, CYP2B6, and CYP3A4/5, extremely low-to-undetectable CYP450 metabolism was observed (24 h), and consistent with their purported 'lack' of metabolic competence. However, for Phase II metabolizing enzymes and metabolic clearance, surprisingly proficient metabolism was observed for bisphenol AF, bisphenol S, and 7-hydroxycoumarin. Here, comparatively low glucuronidation relative to sulfation was observed in contrast to equivalent levels in PHHs. Overall, while a lack of CYP450 metabolism was confirmed in this benchmarking effort, Tox21 cell lines were not 'incompetent' for xenobiotic metabolism, and displayed surprisingly high proficiency for sulfation that rivaled PHHs. These findings have implications for the interpretation of Tox21 assay data, and establish a framework for evaluating of 'metabolic competence' with in vitro models. Highlights: In vitro cell lines used in Tox21 assays were benchmarked for metabolic competence to primary human hepatocyte suspensions. As expected, major CYP450 drug metabolism activities (i.e., CYP1A2, CYP2B6, & CYP3A4/5) using clinical drug substrates revealed extremely low specific activity proficiencies. Surprisingly extensive metabolic clearance with Tox21 cell lines was observed with bisphenol AF, bisphenol S, and 7-hydroxycoumarin that appeared to be driven by Phase II sulfation and disproportionately low glucuronidation proficiency.